Bridging expectations and realities: the future socio- economic impact of AI - Condorelli, Viviana; Beluzzi, Fiorenza (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
This study examines the disconnection between social expectations and corporate investment strategies in AI to understand how economic and technological choices are oriented to meet the population’s needs. Through the analysis of international surveys and recent reports, we explore whether corporate investments respond to social needs and propose the need for a change of perspective towards human-centred AI.